Synthesis And Evaluation Of Geopolymer Properties Using Sago Pith Waste Ash - Rashid, Mohamad Rohaidzat Mohamed (2018)
The sago pith waste (SPW) is a fibrous starch generated from pith of Metroxylon Sagu (Sago Palm), known as an agricultural waste, dumped into nearby rivers without proper treatment, leading to river pollution. Several studies have been conducted to maximize the potential use of SPW and minimize the amount of waste generated by the sago industries. Yet, there is still lack of investigation on the utilization of SPW ashes (SPWA) compared to other agricultural waste materials. Thus, the study of SPWA as an alternative raw material, especially in geopolymer products fabrications requires further investigations. In this work, the optimum SPWA obtained from calcination temperatures (500 C to 1000 C) was used as a partial replacement material (0 to 40 wt. %) in main source material fly ash (FA). These materials are prepared with a combination of sodium hydroxide (NaOH) and sodium silicate (Na2SiO3) as an activator in geopolymer product fabrication. The X-ray florescence (XRF), X-ray diffraction (XRD), Fourier transform infrared (FTIR), mechanical compression testing, and field emission scanning electron microscopy (FESEM) were used as a tools to investigate the viability of SPWA underlying the mechanisms of geopolymerisation. This study revealed that the SPWA mainly composed of CaO and SiO2 with the presence of other oxides such as MgO, Fe2O3, and Al2O3. CaO and SiO2 oxides in SPWA are very significant oxides which are beneficially can be used as an alternative binder for the synthesis of geopolymer products. The compressive strength of geopolymer (GSPWA) mortar at 10% of FA replacement has shown 7% increase compared to normal mortar which utilising on FA as a binder. The highest strength at 28 days is recorded by heat-cured at 65 C (57 kN/m2) followed with oven-cured at 70 C (47 kN/m2) and ambient temperature at 28 C (45 kN/m2). Furthermore, by simple calculations it is shown that the amount of SPWA generated via calcination process is around 0.05 tonne for each tonne of SPW material used. Therefore, the significant of utilizing SPWA as a new alternative raw material especially as a geopolymer product fabrications are two-fold; the waste generated from SPW industry can be manage wisely, whilst the water pollution created by SPW industry can also be minimized.